Discordance Rate in Estrogen Receptor, Progesterone Receptor, HER2 Status, and Ki67 Index Between Primary Unifocal and Multiple Homogenous Breast Carcinomas and Synchronous Axillary Lymph Node Metastases Have an Impact on Therapeutic Decision. Issue 8 (September 2018) - Georgescu, Rares; Boros, Monica; Moncea, Denisa; Bauer, Orsolya; Coros, Marius-Florin; Oprea, Adela; Moldovan, Cosmin; Podoleanu, Cristian; Stolnicu, Simona
Abstract : Background: We aimed to demonstrate that in breast carcinomas the tumor profile is not stable during the metastatic process, with impact on therapeutic decisions. Materials and Methods: We analyzed the estrogen receptor (ER), progesterone receptor (PR), and HER2 status and Ki67 index in 41 primary unifocal (PU) and 37 primary multiple (PM) breast carcinomas with identical immunohistochemical profiles among multiple tumor foci and the matched axillary lymph node metastases. We defined as concordant cases in which the primary tumor (PU or PM) and lymph node metastases displayed identical positivity or negativity for ER, PR, HER2, Ki67 and as discordant cases in which there was a mismatch in at least 1 biological parameter among PU and PM tumor and lymph node metastases. Moreover, we defined as concordant cases in which the molecular profile (based on the immunohistochemical evaluation of ER, PR, HER2, and Ki67) was concordant among PU and PM tumors and lymph node metastases and mismatch cases as those in which the molecular profile of the primary tumor differs from one of the lymph node metastases in at least 1 lymph node. Results: The positivity for the biological markers is not stable during the metastatic process. In this study the total rate of discordant cases was 92.7% in PU tumors and 75.7% in PM homogenous tumors ( P =0.058, odds ratio=0.245, 95% confidence interval, 0.06-0.991). The total rate of shifted cases was 64.9% in PM tumors and 82.9% in PU tumors. The highest rate of shifting was encountered from Luminal B-like to Luminal A-like. In 11 out of 37 (29.7%) PM and in 17 out of 41 (41.5%) PU cases the subtype shifted to a poorer one with respect to prognosis. Conclusions: The patients in whom the primary tumor is hormone receptor and/or HER2 negative but is positive for these markers in the axillary lymph nodes could become eligible for hormonal treatment and/or trastuzumab treatment, which may significantly improve the patient's outcome.